Extrapulmonary tuberculosis: an old but resurgent problem - Baykan, Ali H.; Sayiner, Hakan S.; Aydin, Elcin; Koc, Mustafa; Inan, Ibrahim; Erturk, Sukru M. (Springer Wien, 2022)
Tuberculosis (TB) primarily affects the lungs, but some of its most devastating clinical consequences arise because of its ability to spread from the lungs to other organs. Extrapulmonary TB (EPTB) constitutes 15-20% of all TB cases. Imaging findings are not always specific and can mimic many diseases; therefore, EPTB should be considered in the differential diagnosis, particularly in patients with immune system disorders (AIDS, patients receiving chemotherapy, etc.) and those in other high-risk groups including people with diabetes. The bacterium's passage to the regional lymph nodes is essential for developing a protective T-cell-mediated immune response, but the bacterium can spread hematologically and via the lymphatic system, leading to extrapulmonary involvement. Diagnosis of EPTB in high-risk patients is made based on suspected clinical and radiological findings, but further positive culture and histopathological confirmation may be required in some instances. Radiological evaluations are critical for diagnosis and crucial in planning the treatment and follow-up. This paper aims to review the typical and atypical imaging features and the differential diagnosis of EPTB.
Keywords: Tuberculosis; Extrapulmonary tuberculosis; Magnetic resonance imaging; Computed tomography; X-ray